P3 Novel insights into diminished cardiac reserve in hypertrophic cardiomyopathy from 4D flow CMR component analysis. (21st September 2022) - Ashkir, Z; Lewandowski, AJ; Carlhäll, CJ; Wicks, E; Johnson, S; Hess, A; Mahmod, M; Myerson, S; Ebbers, T; Watkins, H; Neubauer, S; Raman, B
Abstract : Objective: Ventricular flow component analysis using 4D-flow cardiac magnetic resonance (4D-flow CMR) is a novel approach permitting comprehensive haemodynamic evaluation. Abnormal patterns of flow component distribution have been described in dilated and ischaemic cardiomyopathies, and have been linked to functional limitation. This study aimed to characterise ventricular flow component changes in hypertrophic cardiomyopathy (HCM) and assess their relationship with phenotypic severity and predicted sudden cardiac death (SCD) risk. Methods: Fifty-one participants (37 non-obstructive HCM and 14 age, sex & BMI-matched controls) underwent 4D-flow CMR. Left ventricular (LV) end-diastolic volume was separated into four components: direct flow (blood transiting the ventricle within one cycle), retained inflow (blood entering the ventricle and retained for one cycle), delayed ejection flow (retained ventricular blood ejected during systole), and residual volume (ventricular blood retained for over two cycles). Results: HCM patients demonstrated greater direct flow compared to controls (47.5±9% vs 39.4±6%, p=0.003), and reduction in other components. In contrast to controls, HCM exhibited a paradoxical reduction in stroke volume (r=-0.31) with increasing direct flow suggesting diminished cardiac reserve. This direct flow component proportion correlated with LV mass index (r=0.38), end-diastolic volume index (r=-0.42), and SCD risk (r=0.38). Neither LV ejection fraction, nor stroke volume correlated with markers of phenotypic severity. Conclusion: HCM possesses a distinctive pattern of flow component distribution typified by direct flow-stroke volume decoupling, and in keeping with a diminished cardiac reserve. The correlation of direct flow proportion with phenotypic severity and SCD risk highlights its potential as a novel and sensitive haemodynamic measure of cardiovascular risk in patients.